1997
DOI: 10.1089/hum.1997.8.18-2193
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fibronectin-Assisted Retroviral Gene Transfer into Human CD34+Hematopoietic Cells

Abstract: Efficient retroviral gene transfer into hematopoietic stem and progenitor cells can be achieved by co-localizing retrovirus and target cells on specific adhesion domains of recombinant fibronectin (FN) fragments. In this paper, we further optimize this technology for human CD34+ cells. Investigating the role of cytokine prestimulation in retrovirus-mediated gene transfer on plates coated with the recombinant FN CH-296 revealed that prestimulation of granulocyte colony-stimulating factor (G-CSF)-mobilized perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
126
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(131 citation statements)
references
References 55 publications
3
126
1
1
Order By: Relevance
“…LDBM cells were prestimulated for 2 days in IMDM medium (Invitrogen, Carlsbad, CA, USA) supplemented with 10% fetal calf serum Vav1 signaling in hematopoietic progenitor growth Y Gu et al (FCS, HyClone, Logan, UT, USA), 2% penicillin and streptomycin (P/S), and 100 ng/ml of recombinant rat SCF, megakaryocyte growth and development factor (MGDF) and granulocyte colony-stimulating factor (G-CSF) (all from Amgen, Thousand Oaks, CA, USA). Then, retrovirusmediated transduction of LDBM cells was performed by published methods (Hanenberg et al, 1997). At 2 days after transduction, cells were stained with a phycoerythrin (PE)-conjugated anti-mouse CD117 antibody (c-Kit, PharMingen, San Diego, CA, USA).…”
Section: Retroviral Vectors and Transfectionmentioning
confidence: 99%
“…LDBM cells were prestimulated for 2 days in IMDM medium (Invitrogen, Carlsbad, CA, USA) supplemented with 10% fetal calf serum Vav1 signaling in hematopoietic progenitor growth Y Gu et al (FCS, HyClone, Logan, UT, USA), 2% penicillin and streptomycin (P/S), and 100 ng/ml of recombinant rat SCF, megakaryocyte growth and development factor (MGDF) and granulocyte colony-stimulating factor (G-CSF) (all from Amgen, Thousand Oaks, CA, USA). Then, retrovirusmediated transduction of LDBM cells was performed by published methods (Hanenberg et al, 1997). At 2 days after transduction, cells were stained with a phycoerythrin (PE)-conjugated anti-mouse CD117 antibody (c-Kit, PharMingen, San Diego, CA, USA).…”
Section: Retroviral Vectors and Transfectionmentioning
confidence: 99%
“…Recent preclinical work using specific combinations of cytokines 31 and the recombinant fibronectin CH-296 fragment 24 have improved transduction and engraftment to meaningful levels. Our prior experience with transfer of the MDR1 gene by retroviral gene transfer resulted in similar levels of gene transfer between infused and engrafted cell population, with 5-15% of the bone marrow progenitor cells containing vector 1 year after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the transduction protocol was modified to include preloading of the CH-296-coated plates as previous preclinical studies had suggested such vector 'preloading' improved transduction of CD34 þ cells with lower titer virus supernatant. 24 Interestingly, transduction efficiencies for the remaining study participants were not significantly increased but the modifications did appear to significantly increase the transduction of engrafting cells (discussed below).…”
Section: Retroviral Transduction Efficiencymentioning
confidence: 99%
See 2 more Smart Citations